Babylonian Astro-medicine, Quadruplicities and Pliny the Elder - Rumor, Maddalena (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2021)
This article identifies the tradition of Babylonian Kalendertexte as the ultimate source for a passage in Pliny the Elder’s HN 30.95-97, thus establishing a link between Babylonian and Graeco-Roman astral medicine. Implications include the identification of the astrological square aspect (perhaps called é , bītu , "house") in Babylonia, a connection with Hermeticism and the Greek medical theory of Critical Days, and the textual demonstration that Dreckapotheke -names did indeed refer to healing plants, in such a context.